Loyalty and the Effects of Trust and Switching Barriers - Geofakta Razali; Farida Akbarina; Dian Artanti Arubusman; Arief Yanto Rukmana; Muhammad Yusuf (Jurnal Mirai Management, 2023)
In an increasingly cutthroat business environment, companies must be able to choose the right strategy for the company's survival, particularly by marketing their products in accordance with consumers' and customers' wants and expectations. Trust and resistance to change are two factors that consumers/customers take into account when deciding whether or not to remain loyal to a product. This study set out to evaluate the partial impact of trust and mobility limitations on loyalty. The research methods used in this study include descriptive and verification. The population of this study consists of users of Karadenta Skincare products in the city of Sumedang, which also includes the villages of South Sumedang and North Sumedang. For this study, 97 participants were chosen using a purposive sample technique. The distribution of questionnaires served as a method for gathering data. A data instrument's validity and reliability are tested. While the standard assumption test, multiple regression analysis, coefficient of determination analysis, and hypothesis testing are among the data analysis techniques used. Keywords: Trust, Barriers to Movement, and Loyalty.